Effet Antimycobactérien Des Plantes Marocaines: Revue Générale - Zahir, Ilham; Zahir, Atika; Taghiam, Ibtissam (European Scientific Journal, ESJ, 2018)
Tuberculosis is a major public health problem in the world. It is the leading cause of death from infectious diseases. The upsurge of this disease is mainly due to the emergence of multi-resistant and ultra-resistant strains of Mycobacterium tuberculosis. Hence, efforts to find out new antimycobacterial substances are needed. In this context, plants constitute an immense reservoir of original active molecules with interesting biological effects. Hence, they represent a promising way to discover substances that can possibly better control mycobacterial infections and reduce the emergence of bacterial resistance to anti-tubercular drugs. Consequently, our herein work focuses on the presentation of the antimycobacterial activity of the extracts and / or essential oils of 21 Moroccan plants, through the results analysis of scientific investigations carried out between 2007 and 2017 retained via an electronic navigation by using different databases (ScienceDirect, Pubmed, Scopus, Google Scholars and Google), thus revealing the efforts made by Morocco to fight against tuberculosis.